Isolation a new strain of Kocuria rosea capable of tolerating extreme conditions. (June 2015) - Gholami, M.; Etemadifar, Z.; Bouzari, M.
Abstract: A new actinobacterial strain was isolated from Ab-e-Siah spring (dark water) taken from the Ramsar city in Iran, and subjected to several stress conditions investigation. The isolate, named MG2 strain, was Gram-positive, aerobic, diplococci or tetrad shaped, non-spore forming and non-motile. Phylogenetic analysis of the isolate using 16S rDNA sequence indicated that the organism matched best with the genus Kocuria and the highest sequence similarities (98.55%) being found with Kocuria rosea . The 16S rDNA sequence determined in this study has been deposited in the NCBI database with the accession no.JX534199, K . rosea strain MG2. The isolated strain was an alkaliphilic-mesophilic bacterium because the optimal growth was observed at pH 9.2 and temperature of 28 °C under aerobic condition. MG2 was a halotolerant strain and tolerated maximally to 15% NaCl concentraion. Viability analysis by flow cytometry indicated that this strain had highly resistance to UV-C radiation and moderately resistance to desiccation after 28 days. The viability of K . rosea strains MG2 and Deinococcus radiodurans R1 were determined D87 and D98 according to D index, respectively, by a dose radiation 25 J/cm (Appukuttan et al., 2006). Thus the UV resistance of strain MG2 was comparable with representative radiation resistant Deinococcus . Also MG2 was grown at 1–4% of H2 O2 as an oxidant agent. This research is the first study on multiple extreme resistance of Kocuria rosea new strain (MG2) isolated in Iran. Highlights: We have reported a new mesophilic–alkaliphilic radioresistant bacterial strain from radioactive spring Abe-Siah in Ramsar, Iran. The isolate was identified as Kocuria rosea strain MG2 by molecular and phylogenetical analysis. This strain showed high resistance to UV-C radiation and desiccation that analyzed by flow cytometry for cell viability. Also the strain MG2 was resisted to other extreme conditions including: salinity, alkaline pH and hydrogen peroxide.